Stimulating Sunscreen Use Among Outdoor Construction Workers: A Pilot Study - Keurentjes, Anne J.; Kezic, Sanja; Rustemeyer, Thomas; Hulshof, Carel T. J.; van der Molen, Henk F. (Frontiers in Public Health, 2022)
Background: Outdoor workers (OW) receive a higher dose of ultraviolet radiation (UVR) compared to indoor workers (IW) which increases the risk of non-melanoma skin cancer (NMSC). Regular sunscreen use reduces the NMSC risk, however, adequate sun-safety behavior among OW is poor. The main objective was to conduct method- and intervention-related elements of a future intervention trial among OW, based on providing sunscreen and assessing sunscreen use on group- and individual level. Methods: This pilot study was conducted at a construction site in the Netherlands from May-August 2021. Nine dispensers with sunscreen (SPF 50+) were installed at the worksite. OW (n = 67) were invited to complete two (cross-sectional) questionnaires on sun-safety behavior, before and after providing sunscreen. Stratum corneum (SC) samples for the assessment of UV-biomarkers were collected from the forehead and behind the ear from 15 OW and 15 IW. The feasibility of the following elements was investigated: recruitment, (loss to) follow-up, outcome measures, data collection, and acceptability of the intervention. Results: The first questionnaire was completed by 27 OW, the second by 17 OW. >75% of OW were aware of the risks of sun exposure, and 63% (n = 17) found sunscreen use during worktime important. The proportion of OW never applying sunscreen in the past month was 44.4% (n = 12) before, and 35.3% (n = 6) after providing sunscreen. A majority of OW (59.3%, n = 16) found sunscreen provision encouraging for sunscreen use, the dispensers easy to use (64.7%, n = 17) and placed in practical spots (58.8%, n = 18). Collecting SC-samples was fast and easy, and several UV-biomarkers showed higher levels for sun-exposed compared to less exposed body parts. There was no significant difference in UV-biomarker levels between OW and IW. Conclusions: This pilot study revealed low sunscreen use among OW despite providing sunscreen, overall satisfaction with the sunscreen, and the sufficient awareness of the risks of UVR-exposure. Collecting SC-samples at the workplace is feasible and several UV-biomarkers showed to be promising in assessing UVR-exposure. The low participation rate and high loss to follow-up poses a challenge for future intervention studies.